Therapeutic Vaccine for Genital Herpes Simplex Virus-2 Infection: Findings From a Randomized Trial. (30th January 2017) - Bernstein, David I.; Wald, Anna; Warren, Terri; Fife, Kenneth; Tyring, Stephen; Lee, Patricia; Van Wagoner, Nick; Magaret, Amalia; Flechtner, Jessica B.; Tasker, Sybil; Chan, Jason; Morris, Amy; et al.
Abstract: Background: Genital herpes simplex virus type 2 (HSV-2) infection causes recurrent lesions and frequent viral shedding. GEN-003 is a candidate therapeutic vaccine containing HSV-2 gD2∆TMR and ICP4.2, and Matrix-M2 adjuvant. Methods: Persons with genital herpes were randomized into 3 dose cohorts to receive 3 intramuscular doses 21 days apart of 10 µg, 30 µg, or 100 µg of GEN-003, antigens without adjuvant, or placebo. Participants obtained genital swab specimens twice daily for HSV-2 detection and monitored genital lesions for 28-day periods at baseline and at intervals after the last dose. Results: One hundred and thirty-four persons received all 3 doses. Reactogenicity was associated with adjuvant but not with antigen dose or dose number. No serious adverse events were attributed to GEN-003. Compared with baseline, genital HSV-2 shedding rates immediately after dosing were reduced with GEN-003 (from 13.4% to 6.4% for 30 μg [ P < .001] and from 15.0% to 10.3% for 100 µg [ P < .001]). Lesion rates were also significantly ( P < .01) reduced immediately following immunization with 30 µg or 100 µg of GEN-003. GEN-003 elicited increases in antigen binding, virus neutralizing antibody, and T-cell responses. Conclusions: GEN-003 had an acceptable safety profile and stimulated humoral and cellular immune responses. GEN-003 at doses of 30 µg and 100 µg reduced genital HSV shedding and lesion rates. Clinical Trials Registration: NCT01667341 (funded by Genocea).